EVALUASI KEBIJAKAN PENANGGULANGAN HIV/AIDS Di KABUPATEN TANGERANG - Febrianingsih, Gitri; Handayani, Riny (Jurnal PubBis, 2025)
Tangerang Regency has the highest number of HIV/AIDS cases in Banten Province. Thus, the government of Tangerang District has developed a policy on HIV/AIDS prevention, namely Tangerang District Regional Regulation No. 15/2016 on the Prevention of Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome. This study aims to provide an overview of the success of the HIV/AIDS Response Policy in Tangerang District. This research uses a qualitative method with a descriptive approach. The focus of this research is on the Evaluation of HIV/AIDS Response Policy in Tangerang District using William Duun's evaluation theory, namely the criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The data sources in this research are primary and secondary data. This research uses data collection techniques interviews with 7 informants, field observations and documentation studies. The results in this study show that the effectiveness indicator can be said to be effective, seen from the number of new case findings which indicates the number of ODHIV found and given treatment. Then the efficiency indicator can be said to be efficient because there are 44 health services at the Tangerang Regency Health Center. The adequacy indicator can be said to be sufficient because of the cross-sectoral relationship. Furthermore, the equity indicator cannot be said to be evenly distributed because of the lack of health promotion. The implication of this study is that the Tangerang District government should focus more on preventive management and empowerment of NGOs and communities. Keywords : Evaluation, Policy, HIV/AIDS Prevention